Warszawa Teatr Wielki - Bułhak, Jan (1876-1950). (Warszawa, 1951)
Przedstawia Teatr Wielki w Warszawie podczas odbudowy.
Tyt. i data ołówkiem na rewersie.
Keywords: Warszawa (Polska) -- 1945-1970 -- fotografie